Calciphylaxis: a rare cause of limb ulcer – a case report - Cunha, Roberto (2024)
BACKGROUND: Calciphylaxis is a rare disease with a poor prognosis predominantly found in end-stage renal disease patients treated with dialysis. This pathology most commonly presents with painful non-healing ulcers, predisposing to high risk of sepsis and death. The authors present a case of bilateral leg ulcers due to calciphylaxis. CASE REPORT: A 40-year-old female patient presented with painful ulcers in both lower limbs, for two months. She had a history of end-stage renal disease, morbid obesity, severe hypertension, arterial fibrillation and secondary hyperparathyroidism. Duplex examination releveled biphasic curves in the foot arteries. The ankle-brachial index was carried out with a result of 1.1, obtaining a WIFi stage of 3 (2/0/2). Venous disease was excluded. A biopsy was obtained, revealing small thick-walled vessels with dystrophic calcification of the intima and media. After surgical debridement, antibiotics directed at the superimposed infection were administered and local wound care with chemical debridement was performed. The ulcers healed completely after 8 weeks and there was no recurrence after 6 months. CONCLUSION: The diagnosis is made by clinical and histological findings. Treatment involves a multidisciplinary approach with medical treatment and wound care. Drugs such as sodium thiosulphate and cinacalcet have shown good results in the healing of ulcers. Vascular surgeons, as they often deal with patients with leg ulcers, should be aware of calciphylaxis as a differential diagnosis when vascular disease is excluded.